Blood transfusions post kidney transplantation are associated with inferior allograft and patient survival—it is time for rigorous patient blood management - Hassan, Sevda; Mumford, Lisa; Robinson, Susan; Foukanelli, Dora; Torpey, Nick; Ploeg, Rutger J.; Mamode, Nizam; Murphy, Michael F.; Brown, Colin; Roberts, David J.; Regan, Fiona; Willicombe, Michelle (Frontiers in Nephrology, 2023)
Background Patient Blood Management (PBM), endorsed by the World Health Organisation is an evidence-based, multi-disciplinary approach to minimise inappropriate blood product transfusions. Kidney transplantation presents a particular challenge to PBM, as comprehensive evidence of the risk of transfusion is lacking. The aim of this study is to investigate the prevalence of post-transplant blood transfusions across multiple centres, to analyse risk factors for transfusion and to compare transplant outcomes by transfusion status. Methods This analysis was co-ordinated via the UK Transplant Registry within NHS Blood and Transplant (NHSBT), and was performed across 4 centres. Patients who had received a kidney transplant over a 1-year period, had their transfusion status identified and linked to data held within the national registry. Results Of 720 patients, 221(30.7%) were transfused, with 214(29.7%) receiving a red blood cell (RBC) transfusion. The proportion of patients transfused at each centre ranged from 20% to 35%, with a median time to transfusion of 4 (IQR:0-12) days post-transplant. On multivariate analysis, age [OR: 1.02(1.01-1.03), p=0.001], gender [OR: 2.11(1.50-2.98), p<0.0001], ethnicity [OR: 1.28(1.28-2.60), p=0.0008], and dialysis dependence pre-transplant [OR: 1.67(1.08-2.68), p=0.02], were associated with transfusion. A risk-adjusted Cox proportional hazards model showed transfusion was associated with inferior 1-year patient survival [HR 7.94(2.08-30.27), p=0.002] and allograft survival [HR: 3.33(1.65-6.71), p=0.0008], and inferior allograft function. Conclusion RBC transfusions are common and are independently associated with inferior transplant outcomes. We urge that further research is needed to understand the mechanisms behind the outcomes, to support the urgent development of transplant-specific anaemia guidelines.